Examining Nurses’ Theoretical Self-Efficacy and Decision-Making Levels - Serap Güngör Ünal; İsmail Dusak (Global Nursing Insights, 2026)
Aim: This study aimed to determine nurses’ theoretical self-efficacy regarding nursing theories and their decision-making style, and to examine the relationship between these variables. Material and Methods: This descriptive and correlational study was conducted between October 4 and November 4, 2025, with 203 nurses working in nursing care services across Türkiye. Data were collected online using the snowball sampling method and the Nursing Information Form, the Self-Efficacy Scale for Nursing Theories, and the Nurse Decision-Making Scale. The data were analyzed using SPSS version 27, and non-parametric statistical tests were applied. Results: Of the participants, 76.8% reported having previously taken courses related to nursing theories. The mean total score of the Self-Efficacy Scale for Nursing Theories was 3.56±0.84, and the mean total score of the Nurse Decision-Making Scale was 71.60±2.77. No significant correlation was found between the Nurse Decision-Making Scale and the total Self-Efficacy Scale for Nursing Theories (rho=.032, p>.05). However, the total Self-Efficacy Scale for Nursing Theories score was significantly associated with age (p=.025), frequency of reading scientific publications (p=.016), and previous completion of nursing theory courses (p=.007). Conclusions: The results of the study showed that nurses reported theoretical self-efficacy scores around the midpoint of the scale and predominantly exhibited a semi-rational (flexible) decision-making style. Among the nursing theorists most frequently recognized by the participants were Roper, Logan, Tierney, and Florence Nightingale. Nurses’ age, frequency of reading scientific publications, and prior education related to nursing theory courses were found to significantly influence their theoretical self-efficacy. No statistically significant relationship was observed between nurses’ theoretical self-efficacy regarding nursing theories and their decision-making style. Implication for nursing practice: Nurses’ theoretical self-efficacy should be enhanced and their decision-making processes supported to promote systematic and evidence-based care, thereby improving care quality and patient safety.